2010
DOI: 10.1108/17506141011032981
|View full text |Cite
|
Sign up to set email alerts
|

The crisis management in Chinese and Estonian organizations

Abstract: Users who downloaded this article also downloaded: (2006),"Crisis management or crisis response system?: A complexity science approach to organizational crises", Management Decision, Vol. 44 Iss 7 pp. 892-907 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
(43 reference statements)
1
5
0
1
Order By: Relevance
“…Crisis is naturally an unprecedented event that does not give much time to prepare. Crisis, by definition, is "an event, or a set of circumstances that threatens the safety, reputation, or survival of an individual or organization (Junhong & Vanhala, 2010). Crisis as an event includes surprise, threat, and short response time (Tarawneh, 2011).…”
Section: Crisis Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Crisis is naturally an unprecedented event that does not give much time to prepare. Crisis, by definition, is "an event, or a set of circumstances that threatens the safety, reputation, or survival of an individual or organization (Junhong & Vanhala, 2010). Crisis as an event includes surprise, threat, and short response time (Tarawneh, 2011).…”
Section: Crisis Managementmentioning
confidence: 99%
“…CM has been defined as a set of procedures applied in dealing with, containing and resolving emergency situations in a coordinated and planned step (Junhong & Vanhala, 2010). These are measures that the organization has taken to protect it in the event of unforeseen events or situations that may threaten its success or continued operation (Elliott, Harris, & Baron, 2005) and it is the management of business during the crisis period (House, Javidan, & Dorfman, 2001).…”
Section: Crisis Managementmentioning
confidence: 99%
“…The concept of crisis was once seen as an episodic event in the lifecycle of the company, but is now viewed as a normal and regular event (Alas et al, 2009;Bradley, 1978;Cazdyn, 2007;Lalonde, 2007;Rosenthal and Pijnenburg B., 1991;Roux-Dufort, 2007;Sabovic et al, 2010), which must be covered in a risk management strategy (Coombs, 2006;Culasso, 2009;Huber and Scheytt, 2013;Green, 1992;Mitroff and Pearson, 1993).…”
Section: Definition Of the Crisis Phenomenonmentioning
confidence: 99%
“…However, previous researches (Alas et al, 2010b;Gao & Alas, 2010a, b) have shown that HR crisis is one of the three main crisis types in Chinese organizations, preceded by economic and reputational crises. Therefore, it is important to deeply explore human resources crisis in Chinese organizations, so as to gather empirically based knowledge, to complete crisis theory, to provide suggestions and reference to organization management practice.…”
Section: Introductionmentioning
confidence: 96%